2023
DOI: 10.1021/jacs.3c00195
|View full text |Cite
|
Sign up to set email alerts
|

Enabling Peroxygenase Activity in Cytochrome P450 Monooxygenases by Engineering Hydrogen Peroxide Tunnels

Abstract: Given prominent physicochemical similarities between H2O2 and water, we report a new strategy for promoting the peroxygenase activity of P450 enzymes by engineering their water tunnels to facilitate H2O2 access to the heme center buried therein. Specifically, the H2O2-driven activities of two native NADH-dependent P450 enzymes (CYP199A4 and CYP153A M.aq ) increase significantly (by >183-fold and >15-fold, respectively). Additionally, the amount of H2O2 required for an artificial P450 peroxygenase facilitated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 55 publications
1
32
0
Order By: Relevance
“…After the analysis of molecular docking and sequence alignment of HpaB, residues F292, F297, and F301 and loop 209–212 were selected for SM to improve the yield of Pa HpaB to 3-hydroxyphloretin. In addition, ferulic acid and phloretin have similar chemical structures (Figure S1); in the previous study in our laboratory, mutants L213A and Q376N with a higher conversion efficiency to ferulic acid obtained through the substrate channel strategy would also be used in the hydroxylation of phloretin.…”
Section: Resultsmentioning
confidence: 93%
“…After the analysis of molecular docking and sequence alignment of HpaB, residues F292, F297, and F301 and loop 209–212 were selected for SM to improve the yield of Pa HpaB to 3-hydroxyphloretin. In addition, ferulic acid and phloretin have similar chemical structures (Figure S1); in the previous study in our laboratory, mutants L213A and Q376N with a higher conversion efficiency to ferulic acid obtained through the substrate channel strategy would also be used in the hydroxylation of phloretin.…”
Section: Resultsmentioning
confidence: 93%
“…Recently it was demonstrated that engineering H 2 O tunnels to H 2 O 2 tunnels promote peroxygenase activity in CYPs. 48 As Ssca CYP was crystallized in the absence of substrate, we assume the second wider channel to be the substrate and H 2 O 2 channel.…”
Section: Resultsmentioning
confidence: 99%
“…The reactions of acids with bases permeate throughout chemistry. , The resultant acid–base chemistry is very important in areas as diverse as enzyme driven biochemistry, atmospheric chemistry, materials science, basic organic chemistry, organometallic chemistry, and nanochemistry. Owing to both its ubiquity and significance, students learn about the concept of the acid dissociation constant ( K a ) and its logarithmic analogue p K a in various solvents, right from high school . Yet, both experimentally determining p K a values and computing them via simulations continue to be actively pursued as key areas of contemporary research in chemistry. …”
Section: Introductionmentioning
confidence: 99%